Barefoot running step by step : Barefoot Ken Bob, the guru of shoeless running, shares his personal technique for running with more speed, less impact, fewer leg injuries, and more fun /: Barefoot Ken Bob, the guru of shoeless running, shares his personal technique for running with more speed, less impact, fewer leg injuries, and more fun. (2011) - Unknown
No abstract available